2015
DOI: 10.1021/jf505049a
|View full text |Cite
|
Sign up to set email alerts
|

Multi-mycotoxin Analysis of Finished Grain and Nut Products Using Ultrahigh-Performance Liquid Chromatography and Positive Electrospray Ionization–Quadrupole Orbital Ion Trap High-Resolution Mass Spectrometry

Abstract: Ultrahigh-performance liquid chromatography using positive electrospray ionization and quadrupole orbital ion trap high-resolution mass spectrometry was evaluated for analyzing mycotoxins in finished cereal and nut products. Optimizing the orbital ion trap mass analyzer in full-scan mode using mycotoxin-fortified matrix extracts gave mass accuracies, δM, of < ± 2.0 ppm at 70,000 full width at half maximum (FWHM) mass resolution (RFWHM). The limits of quantitation were matrix- and mycotoxin-dependent, ranging f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 46 publications
3
28
0
1
Order By: Relevance
“…AFB1 was found in one sample at 0.45 µg/kg, complying with the regulation regarding maximum limits. Liao, et al [ 23 ] reported contamination with AFB1 at 0.3 µg/kg in one almond sample ( n = 9), similar to the concentration found in this study. Due to the toxicological potential of aflatoxins, special treatments are used in order to eliminate fungal contamination or to inactivate the toxins, such as roasting, sorting, and physical segregation [ 10 ], so it is not usual finding aflatoxins at concentrations above the maximum limits (8 for AFB1 and 10 µg/kg for the sum of aflatoxins).…”
Section: Resultssupporting
confidence: 89%
“…AFB1 was found in one sample at 0.45 µg/kg, complying with the regulation regarding maximum limits. Liao, et al [ 23 ] reported contamination with AFB1 at 0.3 µg/kg in one almond sample ( n = 9), similar to the concentration found in this study. Due to the toxicological potential of aflatoxins, special treatments are used in order to eliminate fungal contamination or to inactivate the toxins, such as roasting, sorting, and physical segregation [ 10 ], so it is not usual finding aflatoxins at concentrations above the maximum limits (8 for AFB1 and 10 µg/kg for the sum of aflatoxins).…”
Section: Resultssupporting
confidence: 89%
“…Проте, не дивлячись на нові розробки в цій технології (а саме високопродуктивна ТШХ, двовимірна ТШХ, високоефективна ТШХ під тиском), тонкошарову хроматографію для кількісного аналізу афлатоксинів замінила високоефективна рідинна хроматографія (ВЕРХ чи HPLC) [7]. Найостаннішими методами для визначення афлатоксинів в кормах та продуктах харчування є високоефективна рідинна хроматографія (HPLC) [12], microHPLC [13], ультра-високоефективна рідинна хроматографія (UHPLC) [14][15][16] або 2D-рідинна хроматографія [17]. Ці методи завдяки високій розподільній можливості дають можливість одночасного розділення не тільки різних афлатоксинів, але також і інших мікотоксинів, таких як охратоксин А, зераленон, Т-2, НТ-2 або інших класів токсинів (наприклад пестицидів).…”
Section: вступunclassified
“…The current determination of FB 1 is primarily achieved by instrumental analysis, enzyme‐linked immunosorbent assay (ELISA) and colloidal gold immunochromatographic assay . However, instrumental analysis and ELISA require expensive equipment and skilled analysts and are unsuitable for rapid on‐site detection of FBs.…”
Section: Introductionmentioning
confidence: 99%